Long-term Deformation Measurements of Atypical Roof Timber Structures - Jiří Bureš; Otakar Švábenský; Marek Kalina (Geoinformatics FCE CTU, 2014)
The paper includes conclusions from evaluation of results obtained from long-termmeasuring of innovative atypical roof timber structures. Based on the results ofmeasurements of vertical and horizontal deformation components it is possible to analyzethe real behavior of structures in given conditions. By assessing deformations in variousstages, including particularly external and internal environment temperatures, relative airhumidity and moisture content of wood, decisive parameters for real structure behaviorcan be established. The data are processed from period 2001 – 2013.